Evidence for the Direct Effect of the NPFF Peptide on the Expression of Feeding-Related Factors in Spotted Sea Bass (Lateolabrax maculatus) - Li, Qing; Wen, Haishen; Li, Yun; Zhang, Zhanxiong; Zhou, Yangyang; Qi, Xin (Frontiers in Endocrinology, 2019)
Neuropeptide FF (NPFF) is a family member of RF-amide peptides, which are suggested to be involved in the control of vertebrate feeding behaviour. However, little is known about the effect of the NPFF peptide on feeding-related processes in basal vertebrates. In this study, four full-length cDNAs, npff, npffr1, npffr2-1 and npffr2-2, were cloned from spotted sea bass and characterized. The conserved NPFF peptide is biologically active because it functionally interacts with different receptors expressed in cultured eukaryotic cells to enhance CRE promoter activity. Tissue distribution analysis showed that the highest npff mRNA expression occurred in the telencephalon, hypothalamus, medulla, gonad and muscle, but the npffrs mRNAs were mainly distributed within the central nervous system (CNS). In situ hybridization (ISH) detected npff-expressing cells in several specific regions ranging across the telencephalon and midbrain to the hypothalamus. Incubation of the spotted sea bass conserved NPFF peptide significantly increased the expression of orexin (orx) and neuropeptide Y (npy) mRNA and decreased the expression of leptin (lep), somatostatin (ss) and cholecystokinin (cck) mRNA in brain cells. Similarly, the conserved NPFF peptide also heightened the expression of gastrin (gas), ghrelin (ghrl), and motilin (mtl) mRNA and significantly reduced the expression of cck mRNA in the intestine and stomach. Taken together, these data suggest that the NPFF peptide may play a stimulating role in regulating feeding-related processes in spotted sea bass.